FABRICATION OF PLATINUM NANOPARTICLE/BORON NITRIDE QUANTUM DOTS/6-METHYL-2-(3-HYDROXY-4-METHOXYBENZYLIDENAMINO)-BENZOTHIAZOLE (ILS) NANOCOMPOSITE FOR ELECTROCATALYTIC OXIDATION OF METHANOL - BEYTUR, Murat (Journal of the Chilean Chemical Society, 2020)
Since worldwide energy demand is growing, conventional fuel reserves are getting low and pollution is increasing, fuel cell applications are becoming more widespread day by day. In this study, preparation of Platinum nanoparticle (PtNPs)/boron nitride quantum dots (BNQDs)/6-methyl-2-(3-hydroxy-4-methoxybenzylidenamino)-benzothiazole (ILs) nanocomposite (PtNPs/BNQDs/ILs) has been made. Afterwards, using various equipment and methods, characterization has been carried out. These equipment and methods are as follows: Transmission Electron Microscope, Scanning Electron Microscope, X-Ray Photo Electron Spectroscopy, Energy-Dispersive X-Ray Spectroscopy and X-Ray Diffraction Method. The catalyst developed on PtNPs/BNQDs/ILs has proven to be cost-effective. Moreover, the PtNPs/BNQDs/ILs nanocomposite has achieved a higher peak for the current oxidation of methanol, when compared to BNQDs/ILs and ILs. Therefore, this catalyst has a better catalytic activity.